2020
DOI: 10.1021/acsomega.0c05119
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Analytical Model Based on the Volumetric Source Method to Production Simulation from Nonplanar Fracture Geometry in Tight Oil Reservoirs

Abstract: Fracturing measures are common practice for horizontal wells of tight oil reservoirs. Thus, production estimation is a significant problem that should be solved. However, previous models for the production of fractured horizontal wells of tight oil reservoirs have some problems. In this paper, we present a semi-analytical model based on the volumetric source method to simulate production from nonplanar fracture geometry in a tight oil reservoir. First, we developed an analytical model based on the volumetric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(60 reference statements)
1
3
0
Order By: Relevance
“…55 A semianalytical model was proposed for tight formation with a nonplanar fracture based on a volumetric source method. 56 These models incorporated multiple flow mechanisms (sorption, diffusion, and stress-sensitivity permeability) for shale gas reservoirs. The models are capable of matching some portions of gas production accurately.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…55 A semianalytical model was proposed for tight formation with a nonplanar fracture based on a volumetric source method. 56 These models incorporated multiple flow mechanisms (sorption, diffusion, and stress-sensitivity permeability) for shale gas reservoirs. The models are capable of matching some portions of gas production accurately.…”
Section: Introductionsupporting
confidence: 56%
“…The stress sensitivity on the matrix and the fracture system found that either the matrix or the fracture subsystem has its passive influence on the transient production rate . A semianalytical model was proposed for tight formation with a nonplanar fracture based on a volumetric source method . These models incorporated multiple flow mechanisms (sorption, diffusion, and stress-sensitivity permeability) for shale gas reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, many researchers have focused on horizontal well oil/gas inflow along the horizontal wells, and this problem involves complex reservoir seepage, wellbore flow, and their relationship. Penmatcha and Aziz and Ozkan et al developed reservoir/well models by the point source function to predict the flow rate and pressure distribution along the horizontal wellbore, and the point source function was also widely used for transient pressure analysis in other gas reservoirs such as the coalbed methane gas reservoir, but the solution of the point source function has the characteristic of singularity . Vicente et al developed a three-dimensional implicit simulator to solve the coupling equation between the reservoir and wellbore.…”
Section: Introductionmentioning
confidence: 99%
“…With the depletion of conventional energy and the increasing demand of humans, unconventional energy exploitation has become a global focus. Sour gas reservoirs are an important part of unconventional gas reservoirs and are widely distributed all over the world. , However, elemental sulfur is often precipitated when the temperature and pressure drop. Elemental sulfur blocks pores, resulting in a decrease in porosity and permeability, and then the production of sour gas wells will be reduced.…”
Section: Introductionmentioning
confidence: 99%